2011
DOI: 10.14483/22487085.3148
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the English Teaching Practice at a Language Institute

Abstract: This study aims to describe the pedagogical practices that take place at the Language Institute of a university based on the observation of classes, questionnaires and interviews of teachers and students. In order to achieve the purpose of the project, the researchers adopted a qualitative approach and also combined an ethnographic perspective which denotes a constant reflection on the part of the teachers who participated as objects of the study. The results of the study demonstrate that most of the teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…They frequently used the textbook as the main source of knowledge and upon which to base their class tasks. In a way, this echoed Bastidas's (2017) and Posada-Ortiz and Patiño-Garzón's (2007) studies in the sense that the teaching of English in Colombia has been textbook-oriented. The teachers mostly used textbooks to teach grammar structures and gap-filling exercises.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They frequently used the textbook as the main source of knowledge and upon which to base their class tasks. In a way, this echoed Bastidas's (2017) and Posada-Ortiz and Patiño-Garzón's (2007) studies in the sense that the teaching of English in Colombia has been textbook-oriented. The teachers mostly used textbooks to teach grammar structures and gap-filling exercises.…”
Section: Discussionmentioning
confidence: 96%
“…In Colombia, recent studies have found that English language teaching at some universities is dominated by some methodologies focused mainly on grammar instruction (Jiménez et al, 2017;Pavas-Amado, 2017;Sánchez-Solarte et al, 2017). Perhaps one exception to such tendency was identified by Posada-Ortiz and Patiño-Garzón (2007), who studied the efl teaching methodology at Universidad del Valle and found that it was based on cooperative learning and the communicative approach. Second, Bastidas (2017), who investigated methods and approaches in efl teaching in Colombian history, found that, mostly, the methodologies have been textbook-oriented.…”
Section: Teachers' Methodological Practices In Efl Education At Universitiesmentioning
confidence: 99%